Dietary docosahexaenoic acid supplementation inhibits acute pulmonary transcriptional and autoantibody responses to a single crystalline silica exposure in lupus-prone mice - Preeti S. Chauhan; Preeti S. Chauhan; Abby D. Benninghoff; Olivia K. Favor; Olivia K. Favor; Olivia K. Favor; James G. Wagner; James G. Wagner; Ryan P. Lewandowski; Lichchavi D. Rajasinghe; Lichchavi D. Rajasinghe; Quan-Zhen Li; et al. (Frontiers in Immunology, 2024)
IntroductionWorkplace exposure to respirable crystalline silica (cSiO2) has been epidemiologically linked to lupus. Consistent with this, repeated subchronic intranasal cSiO2 instillation in lupus-prone NZBWF1 mice induces inflammation-/autoimmune-related gene expression, ectopic lymphoid tissue (ELT), autoantibody (AAb) production in the lung within 5 to 13 wk followed systemic AAb increases and accelerated onset and progression of glomerulonephritis within 13 to 17 wk. Interestingly, dietary docosahexaenoic acid (DHA) supplementation suppresses these pathologic effects, but the underlying molecular mechanisms remain unclear.MethodsThis study aimed to test the hypothesis that dietary DHA supplementation impacts acute transcriptional and autoantibody responses in the lungs of female NZBWF1 mice 1 and 4 wk after a single high-dose cSiO2 challenge. Groups of mice were initially fed a control (Con) diet or a DHA-containing diet (10 g/kg). Cohorts of Con- and DHA-fed were subjected to a single intranasal instillation of 2.5 mg cSiO2 in a saline vehicle (Veh), while a Con-fed cohort was instilled with Veh only. At 1 and 4 wk post-instillation (PI), we compared cSiO2’s effects on innate-/autoimmune-related gene expression and autoantibody (AAb) in lavage fluid/lungs of Con- and DHA-fed mice and related these findings to inflammatory cell profiles, histopathology, cell death, and cytokine/chemokine production.ResultsDHA partially alleviated cSiO2-induced alterations in total immune cell and lymphocyte counts in lung lavage fluid. cSiO2-triggered dead cell accumulation and levels of inflammation-associated cytokines and IFN-stimulated chemokines were more pronounced in Con-fed mice than DHA-fed mice. Targeted multiplex transcriptome analysis revealed substantial upregulation of genes associated with autoimmune pathways in Con-fed mice in response to cSiO2 that were suppressed in DHA-fed mice. Pathway analysis indicated that DHA inhibited cSiO2 induction of proinflammatory and IFN-regulated gene networks, affecting key upstream regulators (e.g., TNFα, IL-1β, IFNAR, and IFNγ). Finally, cSiO2-triggered AAb responses were suppressed in DHA-fed mice.DiscussionTaken together, DHA mitigated cSiO2-induced upregulation of pathways associated with proinflammatory and IFN-regulated gene responses within 1 wk and reduced AAb responses by 4 wk. These findings suggest that the acute short-term model employed here holds substantial promise for efficient elucidation of the molecular mechanisms through which omega-3 PUFAs exert protective effects against cSiO2-induced autoimmunity.